2001
DOI: 10.1161/hy1101.095992
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Femoral Artery Stiffness in Relation to Three Candidate Genes in a White Population

Abstract: Abstract-Different genetic polymorphisms influence cardiovascular disease. We recently discovered a relationship between the intima-media thickness of the muscular femoral artery, but not the elastic common carotid artery, and the combined ACE (ACE, I/D), ␣-adducin (Gly460Trp), and aldosterone synthase (AS, CϪ344T) gene polymorphisms. To investigate the relationship between these polymorphisms and functional properties of the carotid artery and femoral artery, a sample of 756 subjects enrolled in a population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 43 publications
2
73
0
5
Order By: Relevance
“…In the same population the ACE I/D, a-adducin Gly460Trp and aldosterone synthase 344C/T polymorphisms showed significant interactions in relation to the intima-media thickness of the femoral artery [2] and the incidence of hypertension [3]. The hypothesis underlying our previous studies [1,2,3,4] was that these three candidate genes and their interactions lead to structural and/or functional changes in the cardiovascular-renal system via their influence on sodium reabsorption in the kidney and the circulating fluid volume.…”
Section: Introductionmentioning
confidence: 82%
“…In the same population the ACE I/D, a-adducin Gly460Trp and aldosterone synthase 344C/T polymorphisms showed significant interactions in relation to the intima-media thickness of the femoral artery [2] and the incidence of hypertension [3]. The hypothesis underlying our previous studies [1,2,3,4] was that these three candidate genes and their interactions lead to structural and/or functional changes in the cardiovascular-renal system via their influence on sodium reabsorption in the kidney and the circulating fluid volume.…”
Section: Introductionmentioning
confidence: 82%
“…32 Furthermore, increased aortic stiffness as assessed by pulse wave velocity is independently predictive of increase morbidity, CV mortality, and all-cause mortality in patients with hypertension. 33,34 Although the exact mechanisms of aortic stiffening are incompletely understood, blood aldosterone synthase, ACE polymorphisms, [35][36][37] and volume status have been independently associated with pulse wave velocity. 38 Given the roles of aldosterone, angiotensin, and volume expansion in CKD, it is unsurprising that patients with CKD have increased aortic stiffness.…”
Section: Volume Expansionmentioning
confidence: 99%
“…In smokers, median tobacco use was 14 cigarettes per day (interquartile range, [8][9][10][11][12][13][14][15][16][17][18][19][20]. In drinkers, the median alcohol consumption was 10 g day À1 (interquartile range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Table 2 lists the arterial properties by generation and vascular territory.…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…5 Moreover, in ACE DD homozygotes, carriers of mutated ADD1 had higher femoral distensibility and cross-sectional compliance than those with the wild-type ADD1. 6 In the prospective Flemish Study on Environment, Genes and Health Outcomes, the combination of ACE DD homozygosity and mutated ADD1 worsened cardiovascular prognosis to a similar extent as classical risk factors. 7 Experimental studies in fibroblasts from 51 subjects and in transfected cell models showed higher membrane-bound ACE activity in cells carrying the ADD1 Trp allele.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation